The signature based on interleukin family and receptors identified IL19 and IL20RA in promoting nephroblastoma progression through STAT3 pathway - Chen Ding; Hongjie Gao; Liting Zhang; Zhiyi Lu; Bowen Zhang; Ding Li; Fengyin Sun (Scientific Reports)
Abstract Wilms tumor (WT) is a common renal malignancy in pediatric patients. Interleukin (receptors) (IL(R)s) play significant roles in tumor biology, however, their specific involvement in WT remains inadequately understood. We employed univariate Cox regression analysis to screen for certain IL(R) genes associated with prognosis and then analyzed their expression patterns. A prognostic model was constructed based on five selected IL(R)s using the LASSO Cox regression algorithm. To further elucidate the relationship between the prognostic model and the immune microenvironment, we conducted immune-related analyses. Additionally, we performed experiments to verify the roles of IL20RA and IL19 in WT. Finally, CNV, methylation and pan-cancer analysis were performed for IL19 and IL20RA. Our analysis ultimately identified five genes associated with prognosis: IL20RA, IL19, IL24, IL11 and IL17RD. The prognostic model incorporating these five genes demonstrated robust predictive power in both training and validation cohorts. Notably, IL19 and IL20RA were found to promote epithelial-mesenchymal transition (EMT) through the STAT3/SNAIL pathway, thereby contributing to tumor progression. Furthermore, significant differences in immune function and checkpoint expression were observed between the two groups. The high-risk group exhibiting a lower TIDE score, which suggests a potentially better response to immunotherapy. This study introduces a novel IL(R)-based prognostic signature for WT, highlighting IL20RA as a potential therapeutic target. These findings offer valuable insights for future studies on WT.